Verification of infinite-state systems with applications to security - Clarke, Edmund M., Jr. (Edmund Melson), 1945-2020; Minea, Marius; Ţiplea, Ferucio Laurenţiu (NATO security through science series. Information and communication security, 2006)
Provides information for researchers interested in the development of mathematical techniques for the analysis of infinite state systems. The papers come from a successful workshop.